Analysis of Construction Costs For The KH Ahmad Dahlan Pohjentrek Road Section In Pasuruan City Considering Traffic Growth - Rino Wahyu Pamungkas; Budi Witjaksana; Jaka Purnama (International Journal Labs, 2025)
This study analyzes the impact of traffic growth on the structural lifespan and repair costs of the KH Ahmad Dahlan Pohjentrek road section in Pasuruan City. The primary aim is to assess traffic growth, calculate the equivalent single axle load (ESAL), and estimate construction costs using the 2024 Manual of Pavement Design (MDPJ) methodology. The research method involves calculating the ESAL for the road section, estimating construction costs, and recommending solutions to improve road performance. The results show that over a 10-year service life, the cumulative ESAL value is 26,047,040, indicating the need for a durable pavement design. The total construction cost is estimated at IDR 8.6 billion, with the majority of the costs allocated for pavement layers, including AC WC, AC BC, AC Base, and aggregate base courses. Additionally, the study emphasizes the importance of proper drainage management and regular maintenance to extend the lifespan of the pavement and reduce repair costs. In conclusion, the study recommends efficient resource procurement, road widening to alleviate congestion, integration of public transportation programs to reduce traffic dependency, and the implementation of modern monitoring technologies like Weight-in-Motion (WIM) systems to prevent overloading. These recommendations provide actionable insights for policymakers and stakeholders to enhance the road's performance, ensuring sustainable infrastructure development and minimizing future repair costs.